A polyaniline nanofiber array supported ultrathin polyamide membrane for solar-driven volatile organic compound removal. Issue 38 (31st August 2022) - Wei, Xian; Peng, Yubing; Fang, Wangxi; Hu, Zhenyu; Li, Wenwei; Zhang, Shenxiang; Jin, Jian
Abstract : Solar-driven evaporation and molecular sieving processes are integrated to remove volatile organic compounds from water where apolyamide layer supported by the PANI array acts as the molecular sieving layer to intercept VOCs. Abstract : Water-soluble volatile organic compounds (VOCs) widely exist in wastewater and are among the most difficult-to-treat contaminants. Purification and removal of VOCs rely on energy-intensive technologies such as distillation and reverse osmosis, or less efficient approaches such as adsorption and catalytic degradation. An advanced technology that can effectively remove VOCs from water with less energy consumption is highly desired. Here, solar-driven evaporation and molecular sieving processes are integrated to remove VOCs from water where a polyaniline (PANI) nanofiber array acts as a photothermal material to evaporate water, and a polyamide (PA) layer supported by the PANI array acts as the molecular sieving layer to intercept VOCs. The PANI–PA membrane exhibits high VOC rejection and high-water evaporation rates for water containing different kinds of VOCs. When treating water containing 200 mg L −1 phenol, the phenol rejection rate is above 97% and the water evaporation rate is ∼1.0 kg m −2 h −1 under 1 sun irradiation (1 kW m −2 ). Moreover, the PANI–PA photothermal membrane also demonstrates superior VOC removal performance when treating complex wastewater containing acid, base or emulsified oil. The high VOC removal rate, excellent chemical stability and anti-fouling property make the PANI–PA photothermal membrane a promising material for solar-driven water remediation.